On the geometric phenomenology of static friction. (1st August 2017) - Ghosh, Shankar; Merin, A P; Nitsure, Nitin
Abstract: In this note we introduce a hierarchy of phase spaces for static friction, which give a graphical way to systematically quantify the directional dependence in static friction via subregions of the phase spaces. We experimentally plot these subregions to obtain phenomenological descriptions for static friction in various examples where the macroscopic shape of the object affects the frictional response. The phase spaces have the universal property that for any experiment in which a given object is put on a substrate fashioned from a chosen material with a specified nature of contact, the frictional behaviour can be read off from a uniquely determined classifying map on the control space of the experiment which takes values in the appropriate phase space.